Abū Qatāda and Palestine - Nesser, Petter (Die Welt des Islams, 2013)
Abū Qatāda “The Palestinian” is among the most influential ideologues of the salafi-jihadi movement. Born in Palestine, Abū Qatāda grew up in the Jordanian capital Amman, spent time among jihadi guerrillas in Pakistan, and ended up a militant preacher in London. Over the last decade, while going in and out of prison accused of aiding international terrorism, Abū Qatāda has worked to define the theological basis of al-Qaida and likeminded movements. This article explores the Palestinian preacher’s background, activism and ideological communication, focusing on the relationship with his land of origin. It finds that the jihadi thinker seems largely to have ignored his country of origin in both word and deed. This is counter-intuitive given that Abū Qatāda represents a movement presenting the liberation of Palestine as the heart of a worldwide armed holy struggle. However, jihadi ideologues tread a fine line between nationalism and worldliness on one hand, and transnational religious purism on the other.